Determinasi Career Readiness, Personal Branding, dan Etika Kerja terhadap Job Search Intention Mahasiswa Generasi Digital - Nadia, Masyitoh; Maksum, Ikhsan (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2025)
This study aims to examine the determinants of job search intention in final-year college students through the roles of career readiness, personal branding, and work ethic. Tight competition in the job market demands that college graduates possess career readiness, a professional image, and a strong work ethic to enable them to transition optimally into the workforce. This study employed a quantitative approach with a questionnaire-based survey method among final-semester Management students at Maulana Malik Ibrahim State Islamic University of Malang. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the simultaneous and partial effects between variables. The results showed that career readiness, personal branding, and work ethic each had a positive and significant effect on job search intention. These findings indicate that students with high career readiness, the ability to build a professional identity, and positive work values ​​tend to be more active in their job search. This study strengthens the career development literature by confirming that job search behavior is influenced not only by employability skills but also by self-concept and work values ​​in the context of digital generation students. Keywords: career readiness, personal branding, work ethics, job search intention, digital generation Abstrak Penelitian ini bertujuan untuk menguji determinasi job search intention pada mahasiswa tingkat akhir melalui peran career readiness, personal branding, dan etika kerja. Ketatnya persaingan di pasar kerja menuntut lulusan perguruan tinggi memiliki kesiapan karir, citra profesional, serta etika kerja yang baik agar mampu bertransisi ke dunia kerja secara optimal. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei berbasis kuesioner terhadap mahasiswa jurusan Manajemen Universitas Islam Negeri Maulana Malik Ibrahim Malang yang telah memasuki semester akhir. Data dianalisis menggunakan Structural Equation Modeling–Partial Least Square (SEM-PLS) untuk menguji pengaruh simultan dan parsial antar variabel. Hasil penelitian menunjukkan bahwa career readiness, personal branding, dan etika kerja masing-masing berpengaruh positif dan signifikan terhadap job search intention. Temuan ini mengindikasikan bahwa mahasiswa yang memiliki kesiapan karir tinggi, kemampuan membangun identitas profesional, serta nilai kerja positif cenderung lebih aktif dalam mencari pekerjaan. Penelitian ini memperkuat literatur pengembangan karir dengan menegaskan bahwa perilaku pencarian kerja tidak hanya dipengaruhi keterampilan employability, tetapi juga konsep diri dan nilai kerja dalam konteks mahasiswa generasi digital